Consequences of combined exposure to thermal stress and the plasticiser DEHP in Mytilus spp. differ by sex. (September 2021) - Mincarelli, Luana Fiorella; Rotchell, Jeanette M.; Chapman, Emma C.; Turner, Alexander P.; Wollenberg Valero, Katharina C.
Abstract: Little is known about the combined effect of environmental factors and contaminants on commercially important marine species, and whether this effect differs by sex. In this study, blue mussels were exposed for seven days to both single and combined stressors (i.e., +3 °C elevated temperature and two environmentally relevant concentrations of the plastic softener DEHP, 0.5 and 50 μg/l) in a factorial design. Males were observed to be more sensitive to high temperature, demonstrated by the significant increase in out-of-season spawning gonads and higher gene expression of the antioxidant catalase and the estrogen receptor genes. On the other hand, while the gametogenesis cycle in females was more resilient than in males, DEHP exposure altered the estrogen-related receptor gene expression. We show that the combined stressors DEHP and increased temperature, in environmentally relevant magnitudes, have different consequences in male and female mussels, with the potential to impact the timing and breeding season success in Mytilus spp. Highlights: Males and females of Mytilus spp. displayed different responses under thermal stress and exposure to the plasticiser DEHP. Gametogenesis cycle and stress response of males are observed to be more affected by increased temperature. DEHP impairs the gene expression of estrogen receptor-like responses in females. End of the century environmental conditions could impact the reproductive success of Mytilus spp. populations.